2011
DOI: 10.2478/v10181-011-0095-7
|View full text |Cite
|
Sign up to set email alerts
|

The transcriptomic signature of myostatin inhibitory influence on the differentiation of mouse C2C12 myoblasts

Abstract: GDF8 (myostatin) is a unique cytokine strongly affecting the skeletal muscle phenotype in human and animals. The aim of the present study was to elucidate the molecular mechanism of myostatin influence on the differentiation of mouse C2C12 myoblasts, using the global-transcriptome analysis with the DNA microarray technique. Treatment with exogenous GDF8 strongly affected the growth and development of C2C12 mouse myoblasts. This was manifested by the inhibition of proliferation and differentiation as well as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 26 publications
0
12
0
2
Order By: Relevance
“…ITGB1 codes for a subunit of ubiquitous fibronectin receptors and has a number of suggested functions in different tissues. In skeletal muscle, it has been proposed as a possible target for myostatin in mice myoblast differentiation [30] and is also critical for the development of neuromuscular junctions [31] . TMOD1 encodes for tropomodulin, a protein that regulates tropomyosin and F-actin organization.…”
Section: Resultsmentioning
confidence: 99%
“…ITGB1 codes for a subunit of ubiquitous fibronectin receptors and has a number of suggested functions in different tissues. In skeletal muscle, it has been proposed as a possible target for myostatin in mice myoblast differentiation [30] and is also critical for the development of neuromuscular junctions [31] . TMOD1 encodes for tropomodulin, a protein that regulates tropomyosin and F-actin organization.…”
Section: Resultsmentioning
confidence: 99%
“…The deletion of myostatin in mice induces dramatic and widespread increase in skeletal muscle mass due to both muscle hypertrophy and hyperplasia [ 32 ], and it also cause double-muscling phenotype of some cattle and sheep breeds [ 57 ]. Wicik et al [ 67 ] showed inhibitory effect of exogenous MSTN on differentiating C 2 C 12 myoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of high-throughput studies have been performed to explore the functional roles of genes found to have altered expression patterns during skeletal muscle differentiation [ 5 , 24 26 ]. Microarray [ 12 , 27 , 28 ] along with RNA-Seq [ 29 ] studies have improved our knowledge of myogenesis by identifying diverse types of target genes encoding myogenic transcription factors or novel myogenic regulatory factors which govern the fusion of myoblasts into myotubes that were otherwise hard to detect with conventional methods. In spite of these improvements, the roles that these genes play in skeletal muscle development as well as the understanding of underlying molecular mechanisms are still poorly understood.…”
Section: Introductionmentioning
confidence: 99%